The impact of IL-17A inhibitors on scalp and gut microbiota in psoriasis - Huang, Wenxia; Geng, Yuanyuan; Gong, Jie; Wu, Weiwei (Frontiers in Cellular and Infection Microbiology, 2025)
Objective To investigate the differences in scalp and gut microbial diversity, community structure, and specific microbial species in patients with psoriasis vulgaris before and after treatment with interleukin (IL)-17A inhibitors, compared to healthy individuals. Additionally, the preliminary impact of IL-17A inhibitors on scalp and gut microecology was explored. Methods This study utilized 16S rRNA gene sequencing to comparatively analyze the dynamic changes in scalp and gut microbiota diversity and community composition in patients with moderate-to-severe psoriasis vulgaris before and after treatment with IL-17A inhibitors. The study included 15 patients with a Psoriasis Area and Severity Index score of ≥10 and a sex- and age-matched healthy control group. Scalp scale and fecal samples were collected at three-time points: pre-treatment (baseline), 4 weeks post-treatment, and 12 weeks post-treatment. Results IL-17A inhibitors demonstrated favorable efficacy in treating plaque psoriasis. Following treatment, no statistically significant difference was observed in the alpha and beta diversity of the scalp microbiome between patients with psoriasis and healthy controls. Notably, the abundance of harmful bacteria (Pseudomonas species) decreased on the scalp, while beneficial Bifidobacterium levels increased. Regarding gut microbiota, significant differences in α-diversity richness were observed compared to healthy controls (P<0.05). Moreover, the abundance of Roseburia, Megamonas, and the phylum Bacteroidota increased, although the Firmicutes/Bacteroidota (F/B) ratio showed no significant change. Conclusion: IL-17A inhibitor therapy has the potential to improve the structure and diversity of the scalp microbiome, gradually restoring it toward a healthier state while also enhancing gut microbiota diversity. These therapeutic effects may be mediated through immune regulation, such as the Th17 pathway modulation, and microbial metabolites like short-chain fatty acids.